2018
DOI: 10.1063/1.5011960
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of aortic hemodynamics for patients with an abnormal aortic valve: The importance of secondary flow at the ascending aorta inlet

Abstract: Blood flow in the aorta is helical, but most computational studies ignore the presence of secondary flow components at the ascending aorta (AAo) inlet. The aim of this study is to ascertain the importance of inlet boundary conditions (BCs) in computational analysis of flow patterns in the thoracic aorta based on patient-specific images, with a particular focus on patients with an abnormal aortic valve. Two cases were studied: one presenting a severe aortic valve stenosis and the other with a mechanical valve. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 35 publications
8
45
0
Order By: Relevance
“…Briefly, the images were pre-processed using MATLAB to generate a series of files which could be read into Ansys EnSight, where the inlet cross-section was defined by positioning a cut-plane normal to the aortic wall in the ascending aorta. The normal velocity components were then extracted and further processed using our in-house MATLAB tool [21] which included image segmentation and centering; the latter was needed to compensate for in-plane movements of the aorta during the cardiac cycle. Velocity values were then interpolated in time, and mapped onto the 3D global coordinates of the model inlet.…”
Section: B Mr Image Processing and Inlet Boundary Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, the images were pre-processed using MATLAB to generate a series of files which could be read into Ansys EnSight, where the inlet cross-section was defined by positioning a cut-plane normal to the aortic wall in the ascending aorta. The normal velocity components were then extracted and further processed using our in-house MATLAB tool [21] which included image segmentation and centering; the latter was needed to compensate for in-plane movements of the aorta during the cardiac cycle. Velocity values were then interpolated in time, and mapped onto the 3D global coordinates of the model inlet.…”
Section: B Mr Image Processing and Inlet Boundary Conditionmentioning
confidence: 99%
“…For the inlet, these generally involve mapping a typical flow waveform onto flat [4,7,9] or parabolic [6] profiles. Previous studies [20,21] have shown that idealized velocity profiles are not suitable for studies focusing on the ascending aorta and aortic arch, but the descending aorta is less sensitive to the inlet velocity profile.…”
mentioning
confidence: 99%
“…Moreover, the laminar flow condition was assumed in this study due to the constriction of the solver. Although the laminar assumption has been widely used in the flow simulations in the aortic valve and aorta [42,52,80,85,86], its inaccurate estimation of flow parameters within the transitional and turbulent flow regime region should be noted in the individualized evaluations [87].…”
Section: Modeling Simplificationsmentioning
confidence: 99%
“…Uncertainty quantification (UQ) and sensitivity analysis (SA) of cardiovascular modeling have been gaining increasing attention in the past decade. There are numerous literature on examining the influence of variations in inflow/outflow boundary conditions [6][7][8][9][10][11][12][13][14][15][16][17][18], segmented vascular geometry [19][20][21][22][23][24][25][26][27][28], and mechanical properties of blood flow or vessel walls [29][30][31][32][33] on the simulated hemodynamics. However, the majority of these works focused on investigating the sensitivity of the model to its input factors using ad hoc perturbation analysis but have yet to rigorously characterize and quantify the uncertainty distributions.…”
Section: Introductionmentioning
confidence: 99%